Fostamatinib for the treatment of warm antibody autoimmune hemolytic anemia: Phase 2, multicenter, open‐label study. Issue 6 (3rd March 2022) - Kuter, David J.; Rogers, Kerry A.; Boxer, Michael A.; Choi, Michael; Agajanian, Richy; Arnold, Donald M.; Broome, Catherine M.; Field, Joshua J.; Murakhovskaya, Irina; Numerof, Robert; Tong, Sandra
Abstract: Patients with relapsed warm antibody autoimmune hemolytic anemia (wAIHA) have limited treatment options. Fostamatinib is a potent, orally administered spleen tyrosine kinase inhibitor approved in the United States and Europe for the treatment of adults with chronic immune thrombocytopenia (ITP). This phase 2 study evaluated the response to fostamatinib, administered at 150 mg BID orally with or without food in adults with wAIHA and active hemolysis with hemoglobin (Hgb) <10 g/dL who had failed at least one prior treatment. Hemoglobin levels and safety assessments were performed at visits every 2 weeks. The primary endpoint was Hgb >10 g/dL with an increase of ≥2 g/dL from baseline by week 24 without rescue therapy or red blood cell transfusion. Eleven of 24 (46%) patients achieved the primary endpoint. Increases in median Hgb were detected at week 2 and sustained over time. Median lactate dehydrogenase levels and reticulocyte counts generally declined over time with little change in median haptoglobin levels. The most common adverse events (AEs) were diarrhea (42%), fatigue (42%), hypertension (27%), dizziness (27%), and insomnia (23%). AEs were manageable and consistent with the fostamatinib safety database of over 3900 patients across multiple diseases (rheumatoid arthritis, B‐cell lymphoma, COVID‐19, and ITP). No new safety signals were detected. Fostamatinib may be a promising therapeutic option for wAIHA. A randomized, double‐blind, phase 3 study is nearing completion.